Managing hypercholesterolemia and its correlation with carotid plaque morphology in patients undergoing carotid endarterectomy - Kittipan Rerkasem (2018)
Purpose: Hypercholesterolemia is a critical problem in patients with carotid atherosclerosis. The adequacy of attention to lipid risk factors in patients with carotid stenosis awaiting carotid endarterectomy (CEA) has rarely been studied. We also assessed patient awareness of hypercholesterolemia and carotid plaque morphology. Methods: A prospective study was conducted of 141 consecutive patients admitted electively for CEA. Each patient's medical history was taken. Plasma cholesterol concentrations were determined. Plaque histology was scored according to American Heart Association criteria and their modification. Results: Of patients who were aware of their hypercholesterolemia and who were receiving treatment, 28.6% had total cholesterol levels ≥5 mmol/L. Among those patients who had been told that they had no problem with hypercholesterolemia, 32.5% had plasma cholesterol concentrations ≥5 mmol/L. Among those patients who had never had their plasma cholesterol measured, 48.4% had total cholesterol levels ≥5 mmol/L. Patients in this last group tended to have more severe types of plaque pathology than those in other groups (12.9% plaque rupture). Conclusions: Hypercholesterolemia does not seem to be well managed in patients awaiting CEA. © 2008 Rerkasem et al, publisher and licensee Dove Medical Press Ltd.